Magnetic domain imaging of nano‐magnetic films using magnetic force microscopy with polar and longitudinally magnetized tips. Issue 10 (13th July 2016) - Chen, Sy‐Hann; Chang, Yu‐Hsiang; Su, Chiung‐Wu; Tsay, Jyh‐Shen
Abstract: Perpendicular or parallel magnetic fields are used to magnetize the tips used in magnetic force microscopy (MFM). In this process, perpendicular or parallel magnetic dipole moments are produced on the tip plane, thus leading to the formation of polar magnetized tips (PM‐tips) or longitudinally magnetized tips (LM‐tips), respectively. The resolution of an MFM image of a magneto‐optic disk is used for calibration of these tips, and the saturated magnetic fields of the PM‐ and LM‐tips are found to be 2720 Oe and 680 Oe, respectively. Because both tips can simultaneously magnetize the sample during the scanning process when measuring a Co thin film, clear MFM images are captured, which enable the identification of magnetizable regions and the distribution of the magnetic domains on the sample surface. These results will be useful for improving the manufacturing processes required for soft nano‐magnetic film production.